Enhancing Critical Thinking and Character Development through Argumentative Reasoning in High School Students - Fuad, Muhammad; Amala, Istiqomah Ahsanu; Muhammad, Ulul Azmi (Universitas Lampung, 2025)
This study aims to enhance the culture of critical thinking in high schools by identifying the reasoning techniques used by students in written argumentative texts. Employing a qualitative approach with discourse analysis as the theoretical framework, this research investigates how students construct arguments in their writing assignments. Data collection involved analyzing these assignments to identify reasoning techniques. This study identifies four argumentation patterns used by high school students in argumentative writing: (1) C-G-B, (2) C-G-W-B, (3) C-G-B-MQ, and (4) C-G-W-B-MQ, as well as three argumentation techniques: (1) argumentation with examples, (2) argumentation with authority, and (3) argumentation with cause. The C-G-B and C-G-W-B patterns promote analysis, while the C-G-B-MQ and C-G-W-B-MQ patterns encourage synthesis. These argumentation techniques help students evaluate, strengthen logical thinking, and analyze cause-and-effect relationships. Recommendations for enhancing critical thinking skills and character development include incorporating these argumentation patterns into teaching materials and facilitating the learning of diverse argumentation techniques.Keywords: critical thinking, character development, argumentative reasoning, high school students